2022
DOI: 10.24326/asphc.2022.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol Dependent Salt Tolerance Is Related to Clc1 and Nhx1 Gene Expression in Soybean Plants

Abstract: Paclobutrazol (PBZ) enhances plant resistance to salt stress in two ways: directly, by straight clearance of reactive oxygen species; and indirectly by enhancing antioxidant enzyme activity, photosynthetic efficiency, and metabolite content, and by regulating transcription factors associated with stress. However, the regulatory effects of PBZ under salt stress in soybean are still not well explained and need further investigation. With this aim, the combination effect of salinity (250 mM NaCl) and three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This may be associated with the capability of PBZ to induce a non-enzymatic antioxidant pathway (Seckin Dinler et al, 2021) to restore salt damage. Overall, our previous ndings showed that PBZ is also related to the sequestering of Na + and Cl-ions in the vacuole (NHX and ClC1) in soybean leaves (Seckin Dinler et al 2022). Besides this, the combination of IAA and PBZ performed best to reduce MDA content in soybean leaves under salinity, and this reduction was 44.33% at 200 mM and 48.95% at 300 mM.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This may be associated with the capability of PBZ to induce a non-enzymatic antioxidant pathway (Seckin Dinler et al, 2021) to restore salt damage. Overall, our previous ndings showed that PBZ is also related to the sequestering of Na + and Cl-ions in the vacuole (NHX and ClC1) in soybean leaves (Seckin Dinler et al 2022). Besides this, the combination of IAA and PBZ performed best to reduce MDA content in soybean leaves under salinity, and this reduction was 44.33% at 200 mM and 48.95% at 300 mM.…”
Section: Discussionmentioning
confidence: 73%
“…PBZ increases the tolerance of plants to salt stress by reducing the oxidative damage caused by ROS production (Agha et al 2021). Lastly, PBZ application causes a reduction in salt-induced damages and an increase in biomass yield, water status, chlorophyll content, and antioxidant enzymes under salinity in soybean (Seckin Dinler et al 2022).…”
Section: Introductionmentioning
confidence: 99%